Factors Associated with the Implementation of Early Breastfeeding Initiation in Rokan Hilir Regency - Medina Elly Vanda; Fitriani Pramita Gurning (Karya Kesehatan Siwalima, 2026)
Early Breastfeeding Initiation (EBI) is a critical intervention for improving neonatal survival and overall infant health. However, its implementation in several healthcare settings remains suboptimal, as coverage has yet to achieve the expected 100% target. This study aimed to examine the factors influencing the implementation of EBI at a community health center in Rokan Hilir Regency. A quantitative approach was employed using an analytical survey method with a cross-sectional design. The study included 62 midwives selected through total sampling. Data were collected using structured questionnaires and analyzed using chi-square tests and binary logistic regression. The bivariate analysis revealed significant associations between the implementation of EBI and several factors, including midwives’ understanding of EBI policies, clinical skills, healthcare service support, support from other healthcare personnel, perceived family support, and midwives’ attitudes (p < 0.05). Multivariate analysis indicated that midwives’ understanding (p = 0.002, OR = 586.401), clinical skills (p = 0.005, OR = 102.429), and attitudes (p = 0.004, OR = 79.976) were the most influential determinants of EBI implementation. These findings highlight the importance of strengthening midwives’ professional competencies and attitudes to improve the quality of EBI services. Continuous training programs and comprehensive mentoring strategies are recommended to enhance implementation outcomes.